Coating Hydroxyapatite on 316L Stainless Steel Using Electroforesis Deposition Method. (November 2019) - Fadli, Ahmad; Komalasari,; Indriyani, Ines
Abstract: Stainless steel 316L is a metal which used as bone plate, however this metal has low biocompatibility in a human body. For increasing their biocompatibility, the stainless steel 316L need to be coated with hydroxyapatite (HA). The purpose of this research is to study the effect of applied voltage and deposition time on the properties of HA coated 316L stainless steel. Stainless steel 316L was cut into 20×20×1 mm 3 dimension then HA solution was prepared in ethanol solution used magnetic stirrer for 2 hours and 200 rpm. The HA powder was deposited by electrophoretic deposition (EPD) using carbon as anode and stainless steel 316L as cathode. Powder was coated on stainless steel substrate at 40, 50 and 60 volt and deposition time 10, 20, and 30 minutes. Thickness of HA layer on substrate increased, as the time deposition increased with resultof 35 μm, 50 μm and 60 μm at deposition 50 volt and deposition time of 10, 20 and 30 minutes. Thickness HA coatings can decrease the corrosion of stainless steel, in deposition time 10, 20, and 30 minutes is 0.91, 0.704, and 0.56 mpy. at applied voltage 50 volt and deposition time 30 minutes was obtained suitable for bone plate.